Paleo-sedimentary environment and lithofacies of Jurassic Da’anzhai Member in the Central Sichuan Basin-A case study of Well Ren’an 1 - Zhang, Rui; Zhang, Benjian; Wang, Minglei; Zhu, Haihua; Zhang, Shaomin; Tang, Wenqiang; Zhou, Hongfei; Li, Yucong; Bai, Rong; Jia, Min; Zhu, Yiqing; Han, Luyuan (Frontiers in Earth Science, 2023)
Study of the relationship between lithofacies and sedimentary environment of the Da'anzhai Member in the Central Sichuan area is extremely important for the fine exploration of shale oil. In this paper, the lithofacies types of the Da'anzhai Member in the Well Ren’an 1 (or RA1) are divided into six types based on the three-level lithofacies division method of mineral composition-TOC-mineral structure, namely, massive mud-bearing shell limestone lithofacies, thick argillaceous shell limestone lithofacies, laminated clay silt shale lithofacies, thin shell calcareous shale, laminated shell-bearing shale lithofacies and thick clay shale lithofacies. On the basis of the division of lithofacies, four lithological assemblages were identified according to the depositional mechanism: namely, pure shale type, shale interbeded with laminar-thin limestone type (mm scale), shale interbeded with medium-thin shell limestone type (cm level), and interbedded shale and medium thickness shell limestone type (dm level). The Da'anzhai Member of the Well RA1 belongs to the semi-deep lake-shallow lake sedimentary facies, and has experienced a large-scale water transgression-regression system, and the two-phase sedimentary cycles are developed in the vertical direction. As the paleoclimate gradually changed from relatively dry to warm and humid conditions, the water body became deeper, the salinity gradually decreased, and the supply of terrigenous detritus increased as well. Among the 6 types of lithofacies in Well RA1, the thick clay shale lithofacies have the highest TOC content. It is mainly developed in the depositional environment of warm and humid, deep water, quiet, low salinity, and abundant supply of terrigenous clasts. This study can provide theoretical support for the construction of the shale oil depositional system in the Da'anzhai Member of the Sichuan Basin.